Pre-school teaching for creative processes in education for sustainable development – invisible animal traces, purple hands, and an elk container. Issue 3 (22nd February 2022) - Caiman, Cecilia; Hedefalk, Maria; Ottander, Christina
Abstract: Living in the anthropocene requires addressing several challenges. New forms of teaching where experiences of problem solving, creativity and innovation strategies are needed and considered important. This Swedish study contributes with knowledge on pre-school children's creativity processes when working on an authentic, child-initiated sustainability problem about consumption. Teachers' careful listening was important when forming the teaching context for the sustainability problem. A pragmatic perspective on learning and meaning-making is used to identify the significant features of the different phases in the creativity processes. The empirical results show: the importance of affording a creative context with uncoded material for children to transact with; previous experiences have a prominent role when imagining and reaching beyond the ordinary; the importance of teachers' positive aesthetic judgments for sustaining the creative process. In alignment with the idea of learning as participation, the children broadened the consumption topic to contribute with creative outcomes for animals' welfare.